Utilization of processed honey and jaggery as an oral cyto-fixative - Kunal Sah; B J Janardhana Amaranath; Sunira Chandra; Saad Ahmad (Wolters Kluwer Medknow Publications, 2022)
Background: Ethanol is reasonably used as a cyto-fixative. Owing to its confinements, researchers are in search of natural and eco-friendly cytological fixative. The present study was undertaken to evaluate the efficacy of 20% honey and 20% jaggery as a fixative for oral exfoliative cytology. Materials and Methods: Three oral smears were obtained from each individual (n = 60) by gently scraping the buccal mucosa. One smear was fixed in 95% ethanol second smear in 20% processed honey and third smear in 20% jaggery and was stained with Papanicolaou stain. Two separate pathologists who were blinded for the fixative used evaluated the slides based on the five parameters (cell morphology, nuclear and cytoplasmic staining, clarity, and uniformity of staining). Results: In the present study, it was observed that 20% processed honey showed overall promising results followed by Group A (95% alcohol) and Group B (20% jaggery), but no statistically significant difference was observed between the groups. Conclusion: Honey in lower concentration is an excellent alternative to ethanol and jaggery as a fixative for oral exfoliative cytological samples.